Novel B3GALTL mutations in classic Peters plus syndrome and lack of mutations in a large cohort of patients with similar phenotypes. (17th September 2013) - Weh, E.; Reis, L.M.; Tyler, R.C.; Bick, D.; Rhead, W.J.; Wallace, S.; McGregor, T.L.; Dills, S.K.; Chao, M.‐C.; Murray, J.C.; Semina, E.V.
<x xml:space="preserve">Abstract</x> Peters plus syndrome (PPS) is a rare autosomal‐recessive disorder characterized by Peters anomaly of the eye, short stature, brachydactyly, dysmorphic facial features, developmental delay, and variable other systemic abnormalities. In this report, we describe screening of 64 patients affected with PPS, isolated Peters anomaly and PPS‐like phenotypes. Mutations in the coding region of B3GALTL were identified in nine patients; six had a documented phenotype of classic PPS and the remaining three had a clinical diagnosis of PPS with incomplete clinical documentation. A total of nine different pathogenic alleles were identified. Five alleles are novel including one frameshift, c.168dupA, p.(Gly57Argfs*11), one nonsense, c.1234C>T, p.(Arg412*), two missense, c.1045G>A, p.(Asp349Asn) and c.1181G>A, p.(Gly394Glu), and one splicing, c.347+5G>T, mutations. Consistent with previous reports, the c.660+1G>A mutation was the most common mutation identified, seen in eight of the nine patients and accounting for 55% of pathogenic alleles in this study and 69% of all reported pathogenic alleles; while two patients were homozygous for this mutation, the majority had a second rare pathogenic allele. We also report the absence of B3GALTL mutations in 55 cases of PPS‐like phenotypes or isolated Peters anomaly, further establishing the strong association of B3GALTL mutations with classic PPS only.